Constitutive Optimized Production of Streptokinase in Saccharomyces cerevisiae Utilizing Glyceraldehyde 3-Phosphate Dehydrogenase Promoter of Pichia pastoris. (25th September 2013) - Vellanki, Ravi N.; Potumarthi, Ravichandra; Doddapaneni, Kiran K.; Anubrolu, Naveen; Mangamoori, Lakshmi N.
Abstract : A novel expression vector constructed from genes of Pichia pastoris was applied for heterologous gene expression in Saccharomyces cerevisiae . Recombinant streptokinase (SK) was synthesized by cloning the region encoding mature SK under the control of glyceraldehyde 3-phosphate dehydrogenase ( GAP ) promoter of Pichia pastoris in Saccharomyces cerevisiae . SK was intracellularly expressed constitutively, as evidenced by lyticase-nitroanilide and caseinolytic assays. The functional activity was confirmed by plasminogen activation assay and in vitro clot lysis assay. Stability and absence of toxicity to the host with the recombinant expression vector as evidenced by southern analysis and growth profile indicate the application of this expression system for large-scale production of SK. Two-stage statistical approach, Plackett-Burman (PB) design and response surface methodology (RSM) was used for SK production medium optimization. In the first stage, carbon and organic nitrogen sources were qualitatively screened by PB design and in the second stage there was quantitative optimization of four process variables, yeast extract, dextrose, pH, and temperature, by RSM. PB design resulted in dextrose and peptone as best carbon and nitrogen sources for SK production. RSM method, proved as an efficient technique for optimizing process conditions which resulted in 110% increase in SK production, 2352 IU/mL, than for unoptimized conditions.